Germline defects of familial hemophagocytic lymphohistiocytosis-related genes presenting as adult-onset peripheral T-cell lymphoma - Wei, Chong; Zhao, Danqing; Xue, Song; Cai, Hao; Jia, Congwei; Zhou, Daobin; Zhang, Wei (Frontiers in Immunology, 2024)
Germline mutations in genes involved in perforin-granzyme-mediated cytotoxicity such as PRF1, UNC13D, STX11, and STXBP2 were known to cause familial hemophagocytic lymphohistiocytosis (FHL). In this study, we reported a unique group of 3 patients with germline mutations of UNC13D and STX11 genes and presented as adult-onset peripheral T-cell lymphoma (PTCL) with cytotoxic T-cell phenotype and atypical lymphoma presentations. CD107a degranulation assay and NK-cell activity analysis demonstrated impaired cytotoxic function of the NK/T-cells of the patients with FHL-related mutations. Gene expression profile study revealed that up-regulated genes of the cytotoxic T-cells were enriched in autoimmune-related pathways. It was possible that impaired cytotoxic lymphocyte-mediated immune surveillance and autoantigen stimulation may both participate in PTCL oncogenesis. Germline defects of FLH-related genes may represent a novel predisposing factor for PTCLs.